The Influence of Community Participation in Sustainable Tourism Management at Local Destinations: A Bibliometric Analysis - Novianty, Erlinda; Rahmanita, Myrza; Nurbaeti, Nurbaeti (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study analyzes the influence of community participation in sustainable tourism management at local destinations using a bibliometric approach. By utilizing the VOSviewer application, this research identifies research trends, relationships between key concepts, and data-driven recommendations. The study uses 24 articles from the Google Scholar database, selected based on the PRISMA protocol for publications from 2020-2025. The results show that community participation is a key element in supporting sustainable tourism, particularly in the economic, social, and environmental aspects. Network and density visualizations in VOSviewer reveal a strong link between community participation and local economic development, cultural preservation, and environmental management. Community-Based Tourism (CBT) emerges as a strategic model that places local communities as the main actors in destination management. Additionally, capacity building, institutional strengthening, social capital, and government support are identified as factors supporting the successful management of tourism. This study provides practical contributions by offering strategies to enhance inclusivity and sustainability at local destinations. Theoretically, this research enriches the literature on sustainable tourism, particularly regarding the role of communities in achieving long-term sustainability goals.